Estrategias y recursos verbales de las cartas al director en la prensa digital espanola - Rodríguez-Escudero, Inmaculada (Verba hispanica, 2025)
This study examines the discursive realization of communicative components and functions in letters to the editor published in the Spanish digital press as registered in CORPES XXI (RAE). Drawing on a corpus of 32 texts and employing the qualitative data analysis software MAXQDA 24, the discourse analysis describes and interprets the pragmatic characteristics of this genre. The findings highlight the pragmatic competence strategies employed by readers who write to newspapers to defend an opinion, persuade other read-ers, or denounce problems in their letters.
Keywords: análisis del discurso; analiza diskurza; competencia pragmática; corpus linguistics; digital press; discourse analysis; korpusno jezikoslovje; lengua espanola; lingüística de corpus; pragmatic competence; pragmatična kompetenca; prensa digital; Spanish; spletni mediji; španski jezik